Determination of trace levels of organic fining agents in wines: Latest and relevant findings - Bongiorno, David; Avellone, Giuseppe; Napoli, Anna; Mazzotti, Fabio; Piazzese, Daniela; Censi, Valentina; Indelicato, Serena (Frontiers in Chemistry, 2022)
The production of red wine plays a key role in the local and international economies of several nations. During the winemaking process to clarify the final product, before bottling, and to remove undesired substances (proteins, phenols, and tannins), finings agents are commonly added to wines. These substances have a different origin (animal and vegetable proteins or mineral compounds) and they show a potential risk for the health of allergic subjects. For these reasons, the residues of fining agents, constituted by exogenous proteins based on gluten, egg, and milk proteins, should not be present in the final products and their trace residues should be quantified with accuracy. In the last decade, several analytical approaches have been developed for their quantitative determination using different sample treatment protocols and analytical techniques. These methods are based on liquid chromatography coupled with mass spectrometry or enzyme-linked immunosorbent assays (ELISAs). Recently, biosensors have been proposed as a potential alternative to immunoassay approaches allowing rapid, cheap, simple multi-residue detection. This short review aims to report the most recent and relevant findings in the field.